CHARACTERISTICS OF PETIS CATFISH (Clarias batrachus) WITH DIFFERENT CONCENTRATIONS OF CORNSTARCH - Willy Novfrendy Damanik; Mirna Ilza; Mery Sukmiwati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACT Petis is one type of processing that comes from fishery products. Petis is a processed product in the form of pasta which is quite attractive to the public, especially in Java and Madura. The purpose of this study was to determine the characteristics of catfish paste with different concentrations of cornstarch. The method used is the experimental method, the design used is a completely randomized design. With 4 treatments and 3 replications, namely giving cornstarch 0%, 3%, 5%, and 7%. The research method used is an experimental method with a completely randomized design. Parameters observed were organoleptic, yield, viscosity, pH, air, ash, and protein. The best organoleptic value obtained in the A3 treatment was by giving 5% corn flour, with the characteristics of dark brown appearance and no impurities; specific fragrant aroma of catfish petis, good taste, taste of catfish thick and homogeneous texture, and slightly soft. While the chemical properties of the highest water value was obtained in treatment A1 with a value of 48.70%, the highest value in treatment A4 with a value of 1.17%, and the highest protein value in treatment A4 with a value of 22.04%. As for the physical properties, the highest viscosity value was obtained in the A4 treatment with a value of 48.31 cps and a pH value between 5.81-6.15. Keywords: catfish, cornstarch, petis.